2008
DOI: 10.3748/wjg.14.2582
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal EUS-guided FNA biopsy of a presacral chordoma-report of a case and review of the literature

Abstract: AIM:To evaluate the value of plasma N-terminal pro-brain natriuretic peptide (NT-proBNP) level for predicting postoperative atrial fibrillation (AF) in patients undergoing surgery for esophageal carcinoma. METHODS:NT-proBNP levels were measured in 142 patients 24 h before and 1 h after surgery for esophageal carcinoma. All patients having a preoperative cardiac diagnosis by electrocardiogram (ECG), remained under continuous monitoring for at least 48 h after surgery, and then underwent clinical cardiac evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
1
3
0
Order By: Relevance
“… 8) Elevated levels of NT-proBNP have been found to predict occurrence of new AF in subjects obtained from the general population, 9) and postoperative AF in patients undergoing surgery. 10) 11) In this study, we found NT-proBNP levels to be significantly elevated in patients with AF compared to the patients with sinus rhythm. Atrial enlargement and LV diastolic dysfunction were noted in patients with AF.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“… 8) Elevated levels of NT-proBNP have been found to predict occurrence of new AF in subjects obtained from the general population, 9) and postoperative AF in patients undergoing surgery. 10) 11) In this study, we found NT-proBNP levels to be significantly elevated in patients with AF compared to the patients with sinus rhythm. Atrial enlargement and LV diastolic dysfunction were noted in patients with AF.…”
Section: Discussionsupporting
confidence: 47%
“…NT-proBNP has been known to be elevated in cardiac dysfunction and is widely used for both the diagnosis and evaluation of heart failure 8). Elevated levels of NT-proBNP have been found to predict occurrence of new AF in subjects obtained from the general population,9) and postoperative AF in patients undergoing surgery 10)11). In this study, we found NT-proBNP levels to be significantly elevated in patients with AF compared to the patients with sinus rhythm.…”
Section: Discussionmentioning
confidence: 48%
“…Natriuretic peptides have been shown to be predictive for future AF in a number of different clinical settings [8] , [14] , including the general population [7] , [15] . However, no previous study has evaluated its usefulness for the detection of paroxysmal AF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated the usefulness of transrectal endoscopic ultrasonography-guided fine needle aspiration biopsy of a presacral chordoma, although this approach had been previously thought to be a contraindication. 2 Because surgical resection confirms the definite diagnosis, this eliminates the need for biopsy. The posterior (transsacral), anterior (abdominal), and combined pelvic approaches enable good accesses for complete en bloc resection of tumor with adjacent involved structures.…”
Section: Unusual Presentation Of the Retrorectal Neoplasm Masquerading As A Subcutaneous Hip Tumormentioning
confidence: 96%